ANALISIS KINERJA SIMPANG TAK BERSINYAL DI KOTA GORONTALO - Daud, M. Zulkar (Universitas Bina Taruna Gorontalo, 2013)
ABSTRAK To the effect research is subject to be know traffic performance on divergent four Jl. Nani Wartabone – Jl. MH Thamrin – Jl. MT Haryono, and to know traffic arrangement on divergent four Jl. Nani Wartabone – Jl. MH Thamrin – Jl. MT Haryono. This research started by undertaking survey direct goes to location on divergent four Jl. Nani Wartabone Jl. MH Thamrin Jl. MT Haryono. Data those are taken on this observational process as data of primary and secondary data. Primary data to be gotten by observation or direct watch at observational location which is measurement geometrik deviates that cover median's broad and road wide and vehicle survey. Data secondarying to give picture in common about things which gets bearing with object of research which is Road Map, Data Foots Up Gorontalo's Townee, Data foots up Gorontalo's City vehicle and traffic accident data Gorontalo's City. Observational time at the site is done up to one week which is of hits 06.00 18.00 Wita. Base analisis's Result performance deviates, gotten by volumed arithmetic result traffic on the time of day supreme top as big as 1066 kend / the time of day namely on monday hits 16.00 17.00 one lie on dominated Nani Wartabone road by motor vehicle. To assess supreme capacity namely on sunday as big as 3.200smp / the time of day, supreme saturation degree point namely on monday as big as 0,79, tundaan's point supreme namely on monday as big as 12,92, and highest queue Opportunity namely on monday among 25 50. Of analisis's result upon can be gleaned from that this branch still reasonable is utilized for the present since on hour condition culminates to assess saturation Degree is still under 0,85. Key word: Capacity, Degree saturation, Tundaan, Queue opportunity